Reacting to disinformation. The multilevel EU fact-checking approach - Marinella Belluati; Alice Fubini (De Europa, 2022)
The main objective of this article is to investigate the multilevel approach promoted and adopted by the European Union as a response to the fake news phenomenon. On the one hand, the multilevel approach rests on the integration of different territorial levels (local, national and international). On the other hand, it adopts a multi-actor strategy aiming at the hybridisation of competences and increasingly consolidated network strategies, thus trying to overcome the main limitations and inefficiencies of fact-checking and debunking practices.